2019
DOI: 10.1016/j.ultrasmedbio.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Validation of US evaluation of ulcerative colitis activity

Abstract: This study was aimed at validating the inter-rater grading agreement for assessing disease activity in patients with established ulcerative colitis (UC) using transabdominal ultrasonography (US) versus colonoscopy (CS). Fiftyseven patients underwent US and CS at four facilities. UC disease activity was assessed using the original US grading system and CS Matts classification.Initially, the US and CS grades were assessed at each examining facility, and still images and movie clips were re-assessed at the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…[3] Recent epidemiological studies have indicated that the incidence of UC may be rapidly rising in the USA, China, and Europe, representing a growing crisis and a grave threat to global health. [4][5][6] MicroRNAs (miRNAs) are small (18-24 nucleotides) noncoding RNAs that play important regulatory roles in animals and plants and are one of the more abundant classes of gene regulatory molecules in multicellular organisms. miRNAs bind to complementary sequences in the 3′ untranslated region of specific target mRNAs, and can prevent protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Recent epidemiological studies have indicated that the incidence of UC may be rapidly rising in the USA, China, and Europe, representing a growing crisis and a grave threat to global health. [4][5][6] MicroRNAs (miRNAs) are small (18-24 nucleotides) noncoding RNAs that play important regulatory roles in animals and plants and are one of the more abundant classes of gene regulatory molecules in multicellular organisms. miRNAs bind to complementary sequences in the 3′ untranslated region of specific target mRNAs, and can prevent protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Recent epidemiological studies have indicated that the incidence of UC may be rapidly rising in the USA, China, and Europe, representing a growing crisis and a grave threat to global health. [ 4–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was a significant correlation between endoscopic disease activity and increased bowel wall thickness from the TRUST&UC study 27 and moderate correlation with clinical manifestations and histological grade. 7,28 In our study, we found a significant difference in colonic wall thickness between endoscopic quiescent and active groups [0.60 (0.5-0.75) versus 0.80 (0.6-0.93) cm, p = 0.02], but this failed to be involved in the final model. This suggests that bowel wall thickness can indeed reflect lesion activity in UC patients.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, the myriad advantages of US include lack of radiation exposure, non-invasiveness, and costeffectiveness [12,17]. US has recently garnered interest as a useful imaging modality for the diagnosis and follow-up of inflammatory bowel disease [4,[13][14][15][18][19][20]. A PubMed search for studies published from inception to April 2019, with the terms "ultrasonography," "immune checkpoint inhibitor," and "colitis," revealed a lack of reports detailing the US findings of ICI-related colitis.…”
Section: Discussionmentioning
confidence: 99%